Gellan gum/pectin beads are safe and efficient for the targeted colonic delivery of resveratrol - Prezotti, Fabíola Garavello [UNESP] (2018)
This work addresses the establishment and characterization of gellan gum:pectin (GG:P) biodegradable mucoadhesive beads intended for the colon-targeted delivery of resveratrol (RES). The impact of the polymer carrier system on the cytotoxicity and permeability of RES was evaluated. Beads of circular shape (circularity index of 0.81) with an average diameter of 914 μm, Span index of 0.29, and RES entrapment efficiency of 76% were developed. In vitro drug release demonstrated that beads were able to reduce release rates in gastric media and control release for up to 48 h at an intestinal pH of 6.8. Weibull's model correlated better with release data and b parameter (0.79) indicated that the release process was driven by a combination of Fickian diffusion and Case II transport, indicating that both diffusion and swelling/polymer chains relaxation are processes that contribute equally to control drug release rates. Beads and isolated polymers were observed to be safe for Caco-2 and HT29-MTX intestinal cell lines. RES encapsulation into the beads allowed for an expressive reduction of drug permeation in an in vitro triple intestinal model. This feature, associated with low RES release rates in acidic media, can favor targeted drug delivery from the beads in the colon, a promising behavior to improve the local activity of RES.